Kreativitas Santri Dalam Membaca Al-Qur’an Melalui Metode Iqra’ di TPQ At-Taqwa Lampupok Aceh Besar - Muhammad Rizki; Safriadi; Rahmatullah (Jurnal Riset dan Pengabdian Masyarakat, 2023)
Maximizing Al-Qur'an learning with new creativities, then the learning becomes interesting, especially in TPQ children. The creativity of the students in reading the Qur'an is decreasing day by day, this is due to the employer factor. The purpose of this study was to find out how the creativity of the students in reading the Qur'an through the Iqra' method at TPQ At-Taqwa Lampupok, and what the obstacles faced by the students in reading the Al-Qur'an through the Iqra' method were at TPQ At-Taqwa Lampupok. The research method used is a qualitative method, data collection techniques use observation and in-depth interviews, while data analysis techniques used triangulation. The results of the research showed that the creativity of the students in reading the Qur'an through the Iqra method carried out by TPQ At-Taqwa Lampupok was completely successful. This was surely based on the author's considerations from the interview results which could be seen that there were more conveniences compared to the obstacles experienced by TPQ At-Taqwa Lampupok in applying the Iqra method and in developing the creativity of students in reading the Qur'an. The obstacles faced by the students in reading the Qur'an through the Iqra' method were the students often pay because they did not get the teacher's attention, the difference in absorption in which the teacher has to repeat the material a lot, the Al-Qur'an recitation scheduled which is three days a week allowed the students to forget and lack of book packages.